Indicadores do uso de medicamentos na atenção pediátrica em Feira de Santana, BA - Andrade, Kaio Vinicius Freitas de (2009)
The medical prescription is used as a parameter in studies that evaluate the use of medicines in human populations, especially for pediatric patients. For this purpose, the World Health Organization created indicators to describe general medicine prescription practices. This study aimed at describing the profile of the pediatric prescriptions in public primary health care centers, in Feira de Santana, Bahia State, Brazil. The study analyzed 3,167 prescriptions, 53% for the male sex, 76.1% including the age of the patient, higher frequency of systemically used anti-infective, antiparasitic and respiratory system medicines. The average of medicines per prescription was 2.2, 83.8% of generic drugs, 51.5% of antibiotics, 0.6% injecting medicines, 66.9% of essential drugs. Of 4,700 medicines, 69.4% were dispensed. There were no lists of essential medicines in health care services and the key drug availability was of 77%. The results showed a high frequency of antibiotic prescription and na unsatisfactory percentage of essential drugs prescription, showing the necessity of adopting prescriptive practices based on the rational use of drugs and the spread of the local essential drug list.